SEVERE EPILEPTIC ENCEPHALOPATHY OF EARLY CHILDHOOD DUE TO SCN2A MUTATION - I. S. Bachtin; E. D. Belousova; P. A. Shatalov; S. O. Ayvazyan (Эпилепсия и пароксизмальные состояния)
SCN2A mutations are traditionally described in benign infantile seizures. We are describing rather rare case of epileptic encephalopathy associated with incertion of ctg/ctGg in SCN2A. The female child was born at term by normal delivery after non-complicated pregnancy. Seizures started when she was 3 months old as focal tonic, later on myoclonic seizures developed. They were refractory to all used antiepileptic drugs including valproic acid, topiramate, lamotrigine, ethosuximide and tetracoside. At age of two child is mentally retarded and autistic, unable to walk (because of muscular hypotonia), has no active speech and still has asymmetrical tonic and myoclonic seizures. Unspecific modest brain atrophy was revealed by MRI. Metabolic screening, including urine and serum amino acids, organic acids, lactate, was normal. Our case (alongside with others depicted in literature) confirms that spectrum of phenotypes, associated with mutations in SCN2A, is very wide – from benign infantile seizures to severe epileptic encephalopaties leading to mental retardation, motor and speech disorders.